Analysis of Financial Performance with Economic Value Added (EVA) Method, Market Value Added (MVA), And Financial Value Added (FVA) - Rahmah Arafati Masyiyan; Deannes Isynuwardhana (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
EVA, MVA, and FVA analysis techniques are used to see a better and more efficient financial performance of the company. This study aims to determine financial performance based on EVA (Economic Value Added), MVA (Market Value Added), and FVA (Financial Value Added) methods in coal subsector mining companies listed on the Indonesia Stock Exchange in the 2014-2018 period. This study uses a quantitative descriptive method, with a purposive sampling technique in the coal subsector mining companies listed on the IDX and posted operating profit for the 2014-2018 period. The EVA results in this study are 6 companies with share codes of BYAN, DOID, ITMG, PTBA, SMMT, and TOBA which have positive EVA values ​​over the past 5 years. Then from this study there are MVA results that tend to be negative. There are 3 companies with DOID, ITMG, and PTRO stock codes that have negative MVA values ​​every year for a period of 5 years. Then for the FVA value generated in this study, there are 3 companies that have a negative FVA value each year during the study period, those companies are companies with DOID, KKGI, and PTRO stock codes.